Penerapan Konsep Student - Centered Learning dalam Pendidikan Tinggi Studi Kasus pada Bidang Studi Akuntansi - Elisabeth Cintya Santosa (Jurnal Akuntansi)
Business environment nowdays gives a tough challenge for education world. They asks education system to promote component human resource for the employee market. Those challenges make the universities to prepare themselves in order to improve the quality of their education system. therefore, it is needed more effective teaching and learning in the process of improving the quality of education.